PEMUPUKAN DENGAN BAHAN ORGANIK UNTUK MENUJU PERTANIAN YANG BERWAWASAN LINGKUNGAN DESA SEMBALUN LAWANG, NUSA TENGGARA BARAT - Djamhari, Sudaryanto (Jurnal Rekayasa Lingkungan)
Most of people Sembalun Lawang Village have subsistence agriculture sector. The government programs to increase productions and to use an-organic fertilizer and chemical pesticide. To given this production input result to make other the soil low fertility. Is this on proved always from the Soil Laboratory, Mataram University.To increase fertility, there is a way to give organic fertilizer and micro-organism on at time activity soil processing. This a way a technick of agriculture plantation for organic agriculture wich concern in production and mantinence aruond eco-system.Keywords : organic fertilizer, environmently agriculture,